Multi-layered liposomes as optical resonators - Yong, Derrick (2013)
Multi-layered liposomes, comprising a concentric series of lipid bilayers - separated at fixed distances and compartmentalizing aqueous solutions of alternating refractive indices - are proposed as optical Bragg resonators. Seminal work focuses on the feasibility of successive encapsulations coupled with size-control via extrusion. Synthesis criteria for realization of these liposomes were subsequently discussed based on experimental observations. Numerical studies of the proposed structure showed discernible band gaps, qualifying their potential application in biological lasing.